HPV-Associated Malignancy in the Practice of Colorectal Cancer Specialist - S. S. Gordeev (Эпидемиология и вакцинопрофилактика, 2018)
The history of association between HPV and cancer, risk factors, pathogenesis, diagnostics, treatment and prophylaxis of anal intraelithelial neoplasia (AIN) and squamous-cell anal cancer are discussed in this article. Although these conditions are rare, they may become some of the main health hazards in certain groups of patients, such as HIV-infected patients, patients with history of other HPV-related malignancies, patients practicing anal sexual intercourse and patients receiving systemic immunosuppressive therapy. A collaboration of different specialists is necessary in order to develop effective prophylactic measures for HPV-associated malignancies of anal region. There are no estabilished methods for AIN treatment. The use of ointments and local destruction are the most researched treatment methods. Vaccination is already developed as a prophylactic measure. However, a more thorogh research of HPV types in russian population is necessary prior to its wide implementation. Preliminary data favors the use of polivalent vaccines in russian population.